2006
DOI: 10.1055/s-2006-924286
|View full text |Cite
|
Sign up to set email alerts
|

Diversification of CYCLOIDEA‐like TCP Genes in the Basal Eudicot Families Fumariaceae and Papaveraceae s.str.

Abstract: CYCLOIDEA-like genes belong to the TCP family of transcriptional regulators and have been shown to control different aspects of shoot development in various angiosperm lineages, including flower monosymmetry in asterids and axillary meristem growth in monocots. Genes related to the CYC gene from ANTIRRHINUM show independent duplications in both asterids and rosids. However, it remains unclear to what extent this affected the evolution of flower symmetry and shoot branching in these and other eudicot lineages. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 11 publications
(19 reference statements)
3
32
0
Order By: Relevance
“…Genome duplication has recently been detected in Eschscholzia californica, independent from other duplications in monocot and core eudicot lineages (Cui et al, 2006). Consistently, two CYC-like genes were recently found in E. californica (Kö lsch and Gleissberg, 2006); indeed, we found that these two paralogs belong to the PAPACYL1 and PAPACYL2 lineages. This duplication may concern the common ancestor of all the Papaveraceae and account for the two PAPACYL lineages.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Genome duplication has recently been detected in Eschscholzia californica, independent from other duplications in monocot and core eudicot lineages (Cui et al, 2006). Consistently, two CYC-like genes were recently found in E. californica (Kö lsch and Gleissberg, 2006); indeed, we found that these two paralogs belong to the PAPACYL1 and PAPACYL2 lineages. This duplication may concern the common ancestor of all the Papaveraceae and account for the two PAPACYL lineages.…”
Section: Discussionsupporting
confidence: 88%
“…Phylogenetic analyses based on the TCP and R domains using the Arabidopsis genes as outgroup supported the hypothesis that these genes formed two paralogous lineages that we called PAPACYL1 and PAPACYL2. Using a different gene characterization strategy, Kö lsch and Gleissberg (2006) recently obtained two Papaveraceae sequences closely related to the Arabidopsis genes AtTCP2 and AtTCP24. The specific structure of the TCP domain 3# end in these genes may explain that we did not recover such paralogs.…”
Section: Discussionmentioning
confidence: 99%
“…Flower symmetry is generally assessed via the face-on view of a flower at the time of anthesis, and is usually expressed most strongly in the petal and stamen whorls of the flower. Radially symmetrical flowers (figure 1a) display several planes of symmetry that bisect the flower into mirror images, and bilaterally symmetrical flowers ( figure 1d) [38][39][40][41]. Bilateral flower symmetry itself can range from elaborate to subtle patterns of low complexity (reviewed in [6]).…”
Section: Diversity In Floral Symmetrymentioning
confidence: 99%
“…The plane of bilateral symmetry in Fumariodeae flowers is transverse (figure 4), although partial resupination ultimately brings the transverse plane into dorsoventral orientation. In Capnoides, expression of two CYC-lineage paralogues [40,41] is asymmetric, with slightly stronger expression at the base of the outer petal that forms a nectary [76].…”
Section: (B) Rosidsmentioning
confidence: 99%
“…A recent study in legumes, distantly related to A. majus, shows that a CYC homologue LjCYC2 also establishes adaxial identity in the legume flowers (Feng et al 2006). In the basal eudicot family Papaveraceae sensu lato, the duplication and diversification of CYC-like TCP genes are accompanied by their divergence in expression patterns, in which one type of them may play a role in flower symmetry (Kölsch and Gleissberg 2006;Damerval et al 2007). These facts indicate that the basic function of CYC and its homologues seems to be conserved in eudicots, i.e., controlling the development of floral asymmetry.…”
Section: Introductionmentioning
confidence: 99%